Lista con anotaciones de las Angiospermas de la Reserva Biológica Alberto Brenes (microcuencas de lo Ríos San Lorenzo y San Lorencito),Costa Rica - Gómez-Laurito, Jorge; Ortiz, Rodolfo (Lankesteriana: International Journal on Orchidology, 2015)
The Alberto Brenes Biological Preserve is located in northwest Costa Rica, situated on the Caribbean slope with elevations ranging from 800 to 1500 m. This area is subject to high rain fall through- out the year (4500 mm), and a somewhat lower rain fall from February to April. The moderate temperatures (due to elevation and cloud coverage) and the ample rainfall result in a Submontane Evergreen Tropical Rain Forest. This forest can also be considered as a transitional one between Montane Cloud Forest, found at higher elevations, and Lowland Rain Forest characteristic of lower elevations, as would be expected at this elevation. We present an annotated checklist for the Preserve accounting for 137 families of Angiosperms in 483 genera and 1294 species. The families with the most species are Araceae (50), Gesneriaceae (52), Melastomataceae (61), Orchidaceae (208), Rubiaceae (75), and Solanaceae (37). The most species-rich monocot genera are Pleurothallis (34), Anthurium (25) and Maxillaria (23); the most species-rich dicot genera are Peperomia (33), Piper (23), Miconia (16), Ocotea (21) and Psychotria s.s. (15).The following species were described as new from the preserve: Drymonia submarginalis (Gesneriaceae), Ocotea gomezii, Ocotea morae, Povedadaphne quadriporata (Lauraceae), Marlierea mesoamaricana (Myrtaceae), Prosthechea ortizii (Orchidaceae, as Encyclia ortizii), Coccoloba porphy- rostachys, Coccoloba liportizii (Polygonaceae), Rudgea monofructus (Rubiaceae) and Ticodendron incogni- tum (Ticodendraceae); the latter described as a new family too.